2015
DOI: 10.1111/prd.12076
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functions of gingival and mucoperiosteal fibroblasts in oral wound healing and repair

Abstract: Fibroblasts are cells of mesenchymal origin. They are responsible for the production of most extracellular matrix in connective tissues and are essential for wound healing and repair. In recent years, it has become clear that fibroblasts from different tissues have various distinct traits. Moreover, wounds in the oral cavity heal under very special environmental conditions compared with skin wounds. Here, we reviewed the current literature on the various interconnected functions of gingival and mucoperiosteal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 142 publications
(166 reference statements)
1
43
0
3
Order By: Relevance
“…In this study, two cell types, GFs and DPMCs, originating from different anatomical sites and having distinctive roles in regeneration and healing of damaged periodontal (Sisman, Aksoy, Yalcin, & Karaoz, 2016;Smith, Caceres, Martinez, Oyarzun, & Martinez, 2015) and dental pulp tissues (Patil et al, 2014;Rodas-Junco, Canul-Chan, Rojas-Herrera, De-la-Pena, & Nic-Can, 2017;Sonoyama et al, 2008) were assessed for their potential to regenerate gingival connective tissues (lamina propria) (Chiquet et al, 2015) and dental pulp (Huang, Gronthos, & Shi, 2009) in vitro. Such assessment is seen as necessary in predicting a success of restoration of deciduous teeth or traumatized tissues and the formation of tertiary dentin as a protective barrier for dental pulp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, two cell types, GFs and DPMCs, originating from different anatomical sites and having distinctive roles in regeneration and healing of damaged periodontal (Sisman, Aksoy, Yalcin, & Karaoz, 2016;Smith, Caceres, Martinez, Oyarzun, & Martinez, 2015) and dental pulp tissues (Patil et al, 2014;Rodas-Junco, Canul-Chan, Rojas-Herrera, De-la-Pena, & Nic-Can, 2017;Sonoyama et al, 2008) were assessed for their potential to regenerate gingival connective tissues (lamina propria) (Chiquet et al, 2015) and dental pulp (Huang, Gronthos, & Shi, 2009) in vitro. Such assessment is seen as necessary in predicting a success of restoration of deciduous teeth or traumatized tissues and the formation of tertiary dentin as a protective barrier for dental pulp.…”
Section: Discussionmentioning
confidence: 99%
“…The use of both GFs and dental papilla mesenchymal cell (DPMCs) for regenerative purposes was proposed due to the distinctive functional activities of GFs in the regeneration and repair of periodontal tissues (Chiquet, Katsaros, & Kletsas, 2015) and the role of DPMCs in the differentiation of neurons, adipocytes, odontoblasts and osteoblasts (Chiquet et al, 2015;d'Aquino et al, 2007;Gronthos, Mankani, Brahim, Robey, & Shi, 2000;Xu et al, 2013). In addition, both GFs and DPMCs enhance the migration of endothelial cells and formation of blood vessels in their vicinity (Woloszyk, Buschmann, Waschkies, Stadlinger, & Mitsiadis, 2016).…”
mentioning
confidence: 99%
“…Comparably to previous studies, the significant production of hypercellular granulation tissue (Kondo, Niiyama, Yu, & Kuroyanagi, 2012) at 8 days as well as the substantial deposition of highly organized collagen (Gainza et al, 2015) at 16 days illustrates herein the faster healing in rhEGF-treated sites, particularly with the 1 and 10 μg/g regimen at the opposite of the 50 μg/g concentration. Through the activation of mitogen-activated protein kinase-dependent pathways (Smith et al, 2009), not only EGF stimulates gingival fibroblasts to remove fibrin clot (Chiquet, Katsaros, & Kletsas, 2015), but also activates matrix metalloproteins, major ECM-proteolytic enzymes involved in the healing of human acute gingival wounds (Smith et al, 2009). Surprisingly, while fibroblasts are poised to reduce in number during ECM remodelling, these cells were more numerous at PSD16 in sites treated with the concentrations 1 and 10 μg/g, seemingly due to the EGF proliferative effect on these cells as previously reported (Irwin, Schor, & Ferguson, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Normal fibroblast function is critical for the maintenance of periodontal tissues and for optimal wound healing responses. Evidence suggests that cell growth, proliferation, and matrix synthesis play an important role in periodontal wound healing and tissue regeneration . The hemostatic agents used in the present study showed a linear relationship of percentage cytotoxicity with increasing time intervals, where the cytotoxic effects were significantly high at the 24‐hour time point.…”
Section: Discussionmentioning
confidence: 99%